Endoplasmic reticulum—Phagosome contact sites from the cradle to the grave - Ghavami, Mahlegha; Fairn, Gregory D. (Frontiers in Cell and Developmental Biology, 2022)
Phagocytosis is a key component of the innate immune system used to ingest apoptotic cells and microorganisms for their destruction and recycling of macromolecules and the presentation of antigens to cells of the adaptive immune system. The newly formed vacuole or nascent phagosome undergoes a maturation process reminiscent of the classical endocytic maturation process, reaching a highly degradative phagolysosome stage prior to its tubulovesicular breakdown into lysosomes. The process is highly regulated and can be disrupted by various pathogenic organisms. The exchange of proteins, lipids, and other metabolites between organelles, including maturing phagosomes, is enabled by two processes, vesicular and non-vesicular transport at membrane contact sites (MCS). For decades the specific role(s) of the endoplasmic reticulum (ER) in phagocytosis has been the subject of much debate. In parallel, the last two decades have seen a burst in research on the numerous roles of ER contact sites and resident proteins in all aspects of organelle biology. Here, in this minireview, we describe ER-phagosome contact sites' functions from the early stages of particle engulfment to the phagolysosome dissolution into lysosomes. We also discuss several aspects of ER–phagosome contact sites that remain to be explored.